1, 2, 4, 5‐Benzenetetracarboxylate and Bis(pyridyl)‐1, 2, 4‐triazolate as Co‐ligands in Zinc(II) Complexes: Synthesis, Crystal Structure, and Luminescence Properties. Issue 12 (19th June 2013) - Liu, Jian‐Fang; Huang, Fu‐Ping; Bian, He‐Dong; Yu, Qing
Abstract Based on 1, 2, 4, 5‐benzenetetracarboxylate acid (H4L), and mixed with bis(pyridyl)‐1, 2, 4‐triazolate ligands, two novel 3D zinc(II) coordination polymers [Zn3(L)(3, 4′‐bpt)2] (1) [3, 4′‐Hbpt = 1H‐3‐(3‐pyridyl)‐5‐(4‐pyridyl)‐1, 2, 4‐triazole] and [Zn4(OH)2(L)(4, 4′‐bpt)2]·2H2O (2) [4, 4′‐Hbpt = 1H‐3, 5‐bis(4‐pyridyl)‐1, 2, 4‐triazole] were synthesized and characterized by X‐ray crystallography, elemental analysis, and IR spectroscopy. The topological analysis results reveal that 1 can be simplified to a trinodal (3, 4, 10) topology with the short Schläﬂi symbol of (43)(44·62)(418·624·83) and a novel (3, 4, 5)‐connected topology with (63)(42·84)(4·63·86) symbol for 2, respectively. Thermogravimetric properties of 1 and 2 were also measured. In addition, the luminescent properties of 1 and 2 were investigated in the solid state at room temperature.